EMMA WATSON’S MAGIC SPELL IN GENDER EQUALITY: THE USE OF RHETORICAL DEVICES IN “HEFORSHE” CAMPAIGN - Valiantien, Nita Maya (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2015)
A movement to raise awareness towards gender equality issue has been promoted by the UN through the campaign called “HeforShe”.  To influence people toward the issue, Emma Watson, who is famous with her character as Hermione Granger in Harry Potter series, is appointed as the ambassador of this campaign. Emma Watson capability to convey messages about gender equality cannot be underrated. It can be seen from the strategies that she used in presenting her speech, which is in particular called as rhetorical devices. In that case, this paper aims to explore the use of rhetorical devices in Emma Watson’s speech which includes the rule of three, parallelism, and variation of personal pronoun use.Keywords: discourse, speech, rhetorical devices